An insight on B2B firms in the age of digitalization and paperless processes - Oliveira, José (2021)
In recent years and due to market demand and environmental regulations, firms have been changing their procedures regarding document production, handling, and filling. There has been a paradigm change in document sustention in order to attain such changes, from paper-based to electronic forms, resulting in the Digitization and Paperless Office Program (DPOP). The literature on digitization and paperless processes is profuse; nonetheless, it is outdated, uses only single or multiple case study approaches, and is limited to specific industries, such as healthcare or higher education. To overcome this gap, this research analyses the current implementation of the DPOP in five major sectors by using a country scale approach; consequently, this research study contributes to strengthening the literature in this area of knowledge. The methodology used is quantitative and is based on a questionnaire distributed to the most important economic sectors (education, health, trade, industry, and services) in Portugal. The results show that a DPOP positively impacts companies, as it increases profitability and, in most cases, is a sine qua non condition for negotiating with clients. Additionally, it favours companies’ image, reduces costs, and contributes to environmental sustainability. This research provides new insights into how firms using a DPOP may contribute to dematerialization and paper consumption reduction. It is also original as it covers multiple sectors using a country approach.